Resolution and contracts - Garcimartín Alférez, Francisco José; Sánchez Fernández, Sara (Edward Elgar Publishing, 2019)
In response to the financial crisis of 2008, several jurisdictions have laid down special resolution frameworks giving national authorities extraordinary powers to deal with failing financial institutions. This contribution describes the effects of such resolution tools on contracts entered into by the failing institution, including conflict of law aspects. In particular, it focuses on the specific case of close-out netting provisions and financial collateral arrangements, since one of the main consequences of the recent financial crisis has been the review of the privileged status that these instruments used to have. The EU legislation is used as an example of this change of paradigm, which has so far taken place only in relation to resolution scenarios but not for insolvency proceedings.
Keywords: ODS 16 - Paz, justicia e instituciones sólidas